Shrinking democratic space? Crisis of consensus and contentious politics in Uganda. Issue 3 (3rd July 2019) - Khisa, Moses
ABSTRACT: Previously considered a reforming and promising African country, economically and politically, Uganda has in recent years suffered substantial shrinkage of democratic space. This article argues that two factors have been crucial: the gradual breakdown of minimum political consensus forged under a 'broad-based' government which climaxed in a relatively progressive constitution in 1995 and, second, the security imperative accentuated by the war on terror. These two are compounded by the exigencies of incumbent president Museveni's determination to rule for life, the result being erosion of basic democratic institutions, securitisation of politics, criminalisation of political competition and upsurge in contentious politics.